2020
DOI: 10.1086/703047
|View full text |Cite
|
Sign up to set email alerts
|

Superstition, Fertility, and Interethnic Spillovers: Evidence from Peninsular Malaysia

Abstract: This paper documents a strong correlation between fertility and superstition among the Chinese ethnic diaspora in Malaysia and examines the effect of this Chinese adherence to their cultural norm on the fertility behavior and economic outcomes of ethnic Malays. We exploit a short-term change in fertility preferences induced by the Chinese zodiac calendar that leads to a 14.3 percent rise in birth rates during auspicious dragon years. In contrast, Malays-who do not adhere to this belief-reduce their fertility b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Several suggest the increase in fertility has to do with the zodiac superstition (Agarwal et al, 2017;Goodkind, 1991;Mocan & Yu, 2020). 4 Other authors also found impacts on sex ratio (Grech, 2015), female labor supply (Vere, 2008), and fertility and health outcomes of non-believing groups (Beam & Shrestha, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several suggest the increase in fertility has to do with the zodiac superstition (Agarwal et al, 2017;Goodkind, 1991;Mocan & Yu, 2020). 4 Other authors also found impacts on sex ratio (Grech, 2015), female labor supply (Vere, 2008), and fertility and health outcomes of non-believing groups (Beam & Shrestha, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…I estimate the magnitude of dragon and tiger years by running OLS regression of log cohort sizes on dummies for dragon/tiger years and a quadratic time trend. I focus on cohorts born after 1970 as previous researchers have suggested (Beam & Shrestha, 2020; Goodkind, 1991). The top panel of Table 1 presents the estimates on live birth cohort sizes while the bottom panel presents the estimates on school cohort sizes, measured as number of first grade students.…”
Section: Zodiac Years and Cohort Sizesmentioning
confidence: 99%